The hyperglycemia stimulated myocardial endoplasmic reticulum (ER) stress contributes to diabetic cardiomyopathy in the transgenic non-obese type 2 diabetic rats: A differential role of unfolded protein response (UPR) signaling proteins - Lakshmanan, Arun Prasath; Harima, Meilei; Suzuki, Kenji; Soetikno, Vivian; Nagata, Masaki; Nakamura, Takashi; Takahashi, Toshihiro; Sone, Hirohito; Kawachi, Hiroshi; Watanabe, Kenichi (The international journal of biochemistry & cell biology, 2013)
[Display omitted] ► The PERK and ATF6 pathway play dominant roles for ER stress-mediated diabetic cardiomyopathy in non-obese type 2 DM. ► IRE-1α-XBP1 was not involved in the ER stress-mediated diabetic cardiomyopathy in non-obese type 2 DM. ► Differential regulation of UPR might have differential role on lipogenesis regulation. It has been well demonstrated that excessive blood glucose level could be detrimental to the myocardial function through the variety of mechanisms, of which endoplasmic reticulum stress (ERS) could play an unprecedented role through the activation of unfolded protein response (UPR). Recently, reports are coming out with the evidences that UPR signaling proteins are regulated differentially depend on the experimental conditions and cell types. In addition, ERS has been proposed to be closely associated with the regulation of lipogenesis. Therefore, in this study we tried to find out the expressions of myocardial UPR signaling proteins as well as proteins involved in lipid and glucose metabolism in non-obese type 2 diabetic mellitus (DM) condition using Spontaneous Diabetic Torii (SDT) rat. We have found the significant up-regulation of oxidative, nitrosative and ERS marker proteins in the myocardium of the SDT rats, in comparison to its normal (Sprague-Dawley – SD) rats. In addition, the sub-arm of UPR signaling proteins, such as p-PERK, p-eIF2α, ATF6, CHOP/GADD153, TRAF2, apoptotic signaling proteins, such as BAD, cytochrome C, cleaved caspase-7 and -12, were significantly up-regulated in the SDT rats, in comparison to the SD rats. Interestingly, there were no significant changes in the phosphorylation of IRE-1α, and XBP-1 protein expression. In addition, the proteins involved in lipid and glucose metabolisms, such as PPARα, PPARγ, CPT1, PGC-1α except GLUT4, and the proteins involved in insulin signaling, such as p-Akt and p-PI3K were shown significant attenuation in its expressions in the SDT rats, when compared with the SD rats. Taken together, it is suggested that the activation of PERK and ATF6 pathway are the major determinant rather than the IRE-1α-XBP1 pathway for the ERS-mediated metabolic dysfunction, which might eventually leads to diabetic cardiomyopathy in non-obese type 2 DM.